Chromosome homogeneity in populations of Triatoma brasiliensis Neiva 1911 (Hemiptera - Reduviidae - Triatominae) - Panzera Francisco; Pérez Ruben; Nicolini Paula; Hornos Sonia; Costa Jane; Borges Érika; Diotaiuti Liléia; Schofield Christopher J. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
Triatoma brasiliensis is the most important vector of Chagas disease in the semiarid zone of the Northeast of Brazil. Several authors have reported the occurrence of four chromatic patterns with morphological, ecological, and genetic differences. In order to determine the existence of cytogenetic differentiation between these chromatic forms, we analyzed their karyotypes and the chromosome behavior during the male meiotic process. Triatoma brasiliensis shows distinct and specific chromosome characteristics, which differ from those observed in all other triatomine species. However, no cytogenetic differences were observed between the four chromatic forms of T. brasiliensis. The lack of chromosome differentiation among them could indicate that the populations of this species are in a process of differentiation that does not involve their chromosomal organization.